Risk Calculator for Retinopathy of Prematurity Requiring Treatment - Chaves-Samaniego, Maria J.; Garcia Castejón, Mar; Chaves-Samaniego, Maria C.; Solans Perez Larraya, Ana; Ortega Molina, Jose M.; Muñoz Hoyos, Antonio; Garcia Serrano, Jose L. (Frontiers in Pediatrics, 2020)
Importance: Vascular delay that occurs early in the development of retinopathy of prematurity (ROP) is a risk factor that can be compensated by ensuring a good rate of retinal vascularization to avoid ROP that requires treatment. Background: The objective of the present study was to determine the association between ROP that requires treatment and risk factors such as the extent of the temporal avascular area of the retina and the number of days of mechanical ventilation (MV). Design: Observational retrospective case-control study Participants: Two hundred and twenty-eight premature newborns included in the screening protocol for retinopathy of prematurity. Methods: Subjects underwent retinal examination in the 4th and 6th postnatal weeks. Main outcome measures: The temporal avascular area was measured in disc diameters (DD), while the MV time was measured in days of treatment. Results: Patients with a longer MV time had a higher risk of treatment (R2: 24.7, p < 0.0001; increase in risk of 8.1% for each additional day), as did those who showed greater avascular area (R2: 24.7, p < 0.0001; increase in risk of 111% for each additional DD). An online calculator system and a table are presented for calculating the risk of ROP requiring treatment as a function of these two risk factors. Conclusions and relevance: The temporal avascular area of the retina and MV time must be taken into account in the first examination of the newborn to predict the need for ROP treatment.